Efficacy of Ketogenic Diet for Infantile Spasms in Chinese Patients With or Without Monogenic Etiology - Wang, Jun; Zhang, Jie; Yang, Ying; Gao, Kai; Wu, Ye; Zhang, Yuehua; Jiang, Yuwu (Frontiers in Pediatrics, 2022)
Objective The aim of this study was to evaluate the efficacy of the ketogenic diet (KD) for infantile spasms (IS) in patients with and without different causative genetic mutations. Methods We retrospectively evaluated the data of 119 infants with IS who underwent whole-exome sequencing (WES) before KD treatment. The KD efficacy was analyzed at the 16th week after initiation. Patients showing ≥ 50% seizure reduction from baseline and/or the disappeared hypsarrhythmia were considered as the responders. Chi-squared tests or two-sided Fisher's exact tests were performed for categorical data and Mann–Whitney U-tests for non-parametric and continuous data. Results The responder rate to KD in 119 patients was 47.90%. Six different causative monogenic mutations were identified in 32 (26.89%) patients with IS, including CDKL5 (n = 8), ALG13 (n = 3), KCNT1 (n = 8), SLC35A2 (n = 5), PCDH19 (n = 4), and STXBP1 (n = 4). Patients with CDKL5 mutations showed a significantly better response to KD (87.50%) than patients without CDKL5 mutations (p = 0.03). Seven of eight patients with CDKL5 mutations were responders, including five mutations located in functional motifs, and two mutations in the catalytic domain. Conclusion KD therapy was effective in infants with IS. Patients with CDKL5 mutations might have a better response to KD treatment.